A self-gelling powder and its application

By mixing a specific combination of polymer solution with alkylated chitosan, lyophilized and grinding, the self-gelized powder is solved, and the problems of poor hemostasis and insufficient mechanical strength of existing wound healing materials are achieved, and the combination of efficient hemostasis and good mechanical properties is achieved.

CN116650705BActive Publication Date: 2025-03-14QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310371394.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-10
Publication Date
2025-03-14
Estimated Expiration
2043-04-10

AI Technical Summary

Technical Problem

The existing wound healing materials have poor hemostasis effect and insufficient mechanical strength, making it difficult to meet the multiple needs of procoagulation, antibacterial and cell proliferation during wound healing.

Method used

Self-gelized powder was obtained by mixing solution A, solution B and alkylated chitosan solution, lyophilized and grinding. Among them, solution A includes polydiene dimethylammonium chloride and polyethyleneimine, solution B includes sodium polystyrene sulfonate and polyacrylic acid, and alkylated chitosan is used to enhance the mechanical properties and hemostatic effect of the gel.

Benefits of technology

It achieves high hemostasis effect, short gelation conversion time and good mechanical strength of self-gelized powder, and is suitable for the application of wound healing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116650705B_ABST
    Figure CN116650705B_ABST
Patent Text Reader

Abstract

The present invention provides a self-gelling powder and application. The self-gelling powder provided by the present invention is prepared by mixing solution A, solution B and alkylated chitosan solution to obtain a mixed solution, and then freeze-drying and grinding the mixed solution to obtain the self-gelling powder; wherein the solution A comprises a polydimethyl ammonium chloride solution and a polyethyleneimine solution; and the solution B comprises a sodium polystyrene sulfonate solution and a polyacrylic acid solution. The present invention selects alkylated chitosan as a raw material, selects specific solution A and solution B, uniformly mixes the three solutions, freeze-dries, and obtains the self-gelling powder. Experimental results show that the freeze-dried powder provided by the present invention has a strong hemostatic effect, a short gelation conversion time, and good mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical biomaterials, in particular to an in-situ formed self-gelling powder and application thereof. Background Art

[0002] Wound healing is a physiological process that the body spontaneously initiates after trauma and plays an important role in maintaining skin integrity. It usually includes four consecutive and overlapping physiological processes, including hemostasis, inflammation, regeneration and remodeling. Improper wound healing may lead to hypertrophic scars and ulcers, and even infection and death. In recent years, intervention in wound healing has attracted widespread attention in healthcare fields such as biomaterials and tissue engineering. Therefore, the ideal wound healing therapeutic material should have excellent procoagulant and antibacterial abilities, as well as good cell proliferation effects, so that it can participate in each of the four stages. In recent years, a variety of functional materials for wound treatment have been developed, including porous sponges, micro / nano hydrogel particles, biocompatible hydrogels, synthetic fibers, and liposomes.

[0003] So far, the commonly used traditional wound treatment materials have more or less certain defects. For example, in terms of wound moisturizing, conventional gauze, hemostatic powder, etc. are not effective. In addition, some patch materials have certain skin irritation when used.

[0004] Polyethyleneimine (PEI) and polyacrylic acid (PAA) are common cationic polymers and anionic polymers. When PEI / PAA absorbs water, it can quickly form a viscous hydrogel through physical cross-linking, which can not only absorb blood, but also form a relatively stable physical barrier at the wound, and has good flexibility. It can provide a moist environment for the wound, which helps to stop the bleeding of the wound and is an ideal wound dressing. Polydimethylammonium chloride (PDDA) and sodium polystyrene sulfonate (PSS) can form nanoparticles in situ in the polymer hydrogel skeleton. There is a non-covalent interaction between the nanoparticles and the polymer matrix, which can simultaneously enhance the tensile strength and tensile toughness of the polymer material, and significantly enhance the gel's ability to resist blood pressure. However, the currently disclosed gel-based wound healing materials have poor hemostatic effects. Therefore, it is of great significance to provide a wound healing material that has not only good mechanical strength but also good hemostatic effects. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a self-gelling powder and application thereof. The self-gelling powder provided in the present invention has good hemostatic effect and good mechanical strength.

[0006] Compared with the prior art, the present invention provides a self-gelling powder and application. The self-gelling powder provided by the present invention is obtained by mixing solution A, solution B and alkylated chitosan (ACS) solution to obtain a mixed solution, and then freeze-drying the mixed solution and grinding to obtain the self-gelling powder; wherein the solution A includes a polydimethyl ammonium chloride solution and a polyethyleneimine solution; and the solution B includes a sodium polystyrene sulfonate solution and a polyacrylic acid solution. The present invention selects alkylated chitosan as a raw material, selects specific solution A and solution B, uniformly mixes the three solutions, freeze-dries, and obtains a self-gelling powder. Experimental results show that the freeze-dried powder provided by the present invention has a strong hemostatic effect, a short gelation conversion time, and good mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 This is the infrared spectrum of the alkylated chitosan prepared in Example 1 of the present invention;

[0008] Figure 2 This is a test graph of the hydrogel modulus of polyethyleneimine solution and polyacrylic acid solution in different proportions prepared in Example 3 of the present invention;

[0009] Figure 3 This is a test graph of the hydrogel modulus with different alkylated chitosan contents prepared in Example 5 of the present invention;

[0010] Figure 4 This is a test graph of the viscosity of hydrogels with different alkylated chitosan contents prepared in Example 5 of the present invention;

[0011] Figure 5 This is a test graph of the hydrogel modulus with different contents of polydiallyl dimethyl ammonium chloride and sodium polystyrene sulfonate prepared in Example 7 of the present invention;

[0012] Figure 6 This is a test graph of the viscosity of hydrogels with different contents of polydiallyl dimethyl ammonium chloride and sodium polystyrene sulfonate prepared in Example 7 of the present invention;

[0013] Figure 7 is the gel transition time of the in-situ self-gelling powder containing different alkylated chitosans;

[0014] Figure 8 Schematic diagram of hydrogel synthesis;

[0015] Fig. 9 The image and scanning electron microscope image of the in-situ self-gelling powder prepared in Example 11 of the present invention;

[0016] Fig.10 The hemolysis rate results of the self-gelling powder and its components are prepared;

[0017] Fig.11 To prepare the cell proliferation rate results of the obtained self-gelling powder and its components;

[0018] Fig.12 To prepare the antibacterial rate of the obtained self-gelling powder and its components against Escherichia coli and Staphylococcus aureus;

[0019] Fig.13 In vitro clotting time of the self-gelling powder and its components obtained for preparation;

[0020] Fig.14 The actual picture of in vitro coagulation of the self-gelling powder and its components obtained for preparation;

[0021] Fig.15 The results of the rat wound healing model experiment using the prepared self-gelling powder and its components. DETAILED DESCRIPTION

[0022] The present invention provides a self-gelling powder, which is prepared by mixing solution A, solution B and alkylated chitosan solution to obtain a mixed solution, and then freeze-drying and grinding the mixed solution to obtain the self-gelling powder;

[0023] Wherein, the solution A comprises a polydimethyl ammonium chloride solution and a polyethyleneimine solution;

[0024] The B solution includes a sodium polystyrene sulfonate solution and a polyacrylic acid solution.

[0025] According to the present invention, the alkylated chitosan is preferably one or more of dodecyl chitosan, tetradecyl chitosan, hexadecyl chitosan and octadecyl chitosan, more preferably dodecyl chitosan, tetradecyl chitosan, hexadecyl chitosan or octadecyl chitosan, and most preferably dodecyl chitosan; the initial concentration of the alkylated chitosan solution is 0.2wt% to 1wt%, more preferably 0.4wt% to 0.8wt%, and most preferably 0.6wt%; in the mixed solution, the alkylated chitosan solution preferably accounts for 8 to 15% of the total volume, more preferably 10 to 13%;

[0026] In the present invention, the preparation method of the alkylated chitosan preferably comprises the following steps:

[0027] providing a chitosan solution;

[0028] Adding dodecanal, tetradecanal, hexadecanal and octadecanal dropwise into the chitosan solutions of each group, respectively, and carrying out condensation reaction under acidic conditions to obtain four groups of imidized chitosan;

[0029] The four groups of imidized chitosans are mixed with a reducing agent to carry out a reduction reaction to obtain long-chain alkylated chitosans.

[0030] In the present invention, the mass concentration of chitosan in each group of chitosan solutions is preferably 10.0 g / L; the chitosan solution preferably includes chitosan, acetic acid solution and ethanol. The concentration of the acetic acid solution is preferably 2 wt%; the volume ratio of the acetic acid solution to ethanol is preferably 1:1.

[0031] After obtaining the chitosan solution, the present invention drips dodecanal to octadecanal into each group of chitosan solutions for condensation reaction to obtain different imidized chitosans. In the present invention, the acidic condition is provided by an acetic acid solution. The temperature of the chitosan solution during the dripping is preferably 45° C.; the dripping is preferably dropwise addition. The ratio of the four fatty aldehydes to chitosan is calculated according to the molar ratio of the aldehyde group in the fatty aldehyde and the amino group in the chitosan, preferably 0.125 to 0.5:1, more preferably 0.125:1, 0.25:1 or 0.5:1. The time of the condensation reaction is preferably 4 hours.

[0032] After the condensation reaction, the present invention preferably cools the reaction solution to room temperature to obtain imidized chitosan.

[0033] After obtaining four groups of imidized chitosan, the present invention mixes the imidized chitosan with a reducing agent for reduction reaction to obtain four groups of long-chain alkylated chitosan. In the present invention, the reaction solution of the condensation reaction is not post-treated and is directly mixed with the reducing agent. In the present invention, the reducing agent is preferably sodium borohydride, and the molar ratio of the sodium borohydride to the aldehyde group in the fatty aldehyde is preferably 3:1. In the present invention, the reducing agent is preferably used in the form of a reducing agent solution, and the mixing is preferably dripping the reducing agent solution into the four groups of imidized chitosan. The temperature of the reduction reaction is preferably room temperature; the time of the reduction reaction is preferably 3h.

[0034] In the present invention, chitosan is condensed with fatty aldehyde to obtain imidized chitosan, which is then reduced with sodium borohydride to obtain alkylated chitosan.

[0035] After the reduction reaction, the present invention preferably performs post-treatment on the obtained reduction reaction product to obtain long-chain alkylated chitosan. In the present invention, the post-treatment preferably comprises the following steps:

[0036] adjusting the pH value of the reduction reaction product to 10 to precipitate a solid;

[0037] The solid is centrifuged and washed to obtain a neutral solid;

[0038] The neutral solid is dissolved in an acetic acid solution, and the obtained solution is stored at low temperature and then filtered under pressure to obtain a decontaminated solid;

[0039] The pH value of the impurity-removed solid is adjusted to 10, and the precipitate is separated by centrifugation;

[0040] The precipitate is washed with water until it is neutral and then freeze-dried to obtain four groups of long-chain alkylated chitosan.

[0041] In the present invention, sodium hydroxide solution is preferably added to the reduction reaction product to adjust the pH value, and the concentration of the sodium hydroxide solution is preferably 4wt%.

[0042] In the present invention, the centrifugal washing is preferably three times of methanol washing and three times of ethanol washing, and finally washing with water until neutral;

[0043] After obtaining the neutral solid, the present invention preferably dissolves the neutral solid in an acetic acid solution with a concentration of 2 wt %; the temperature of the low-temperature storage is preferably 4° C.; and the time of the low-temperature storage is preferably 30 min.

[0044] In the present invention, the pH value of the impurity-removing solid is preferably adjusted by adding the impurity-removing solid into a sodium hydroxide solution to adjust the pH value to 10.

[0045] Through experimental research of the present application, it is found that the chitosan provided by the present invention, by introducing a long-chain alkyl carbon chain on the amino group of the chitosan side chain, can be embedded in the cell membrane to form a chitosan-blood cell gel network structure, thereby enhancing the hemostatic effect of the powder.

[0046] According to the present invention, in solution A, the initial concentration of the polyethyleneimine solution is 5-8wt%, more preferably 6-7wt%; the initial concentration of the polydiallyl dimethyl ammonium chloride solution is preferably 7-12wt%, more preferably 8-10wt%.

[0047] According to the present invention, in solution B, the initial concentration of the polyacrylic acid solution is preferably 5-8wt%, more preferably 6-7wt%; the initial concentration of the sodium polystyrene sulfonate solution is 9-12wt%, more preferably 10-11wt%, and most preferably 10.3-10.5wt%.

[0048] According to the present invention, in the mixed solution, the added polydiallyl dimethyl ammonium chloride solution preferably accounts for 3-7% of the total volume, more preferably 5-6%, the added polyethylene imine solution preferably accounts for 38-42% of the total volume, more preferably 40%-41%; the added sodium polystyrene sulfonate solution preferably accounts for 3-7% of the total volume, more preferably 5-6%, and the polyacrylic acid solution preferably accounts for 38-42% of the total volume, more preferably 40%-41%. In the present invention, the volume ratio of the added polyethylene imine solution and the added polyacrylic acid solution is preferably (3-7): (7-3), preferably 3:7, 4:6, 5:5, 6:4, 7:3, more preferably 5:5; the volume ratio of the added polydiallyl dimethyl ammonium chloride (PDDA) solution to the added sodium polystyrene sulfonate (PSS) solution is preferably 1:1.

[0049] According to the present invention, the weight average molecular weight of the polyethyleneimine (PEI) is preferably 65,000 to 75,000, more preferably 70,000; the weight average molecular weight of the polyacrylic acid (PAA) is preferably 230,000 to 250,000, more preferably 240,000; the weight average molecular weight of the polydimethyl ammonium chloride (PDDA) is preferably 80,000 to 150,000, more preferably 100,000; the weight average molecular weight of the sodium polystyrene sulfonate (PSS) is preferably 65,000 to 75,000, more preferably 70,000.

[0050] The present invention also provides an application of the self-gelling powder described in the present application in preparing wound treatment materials. The wound treatment material prepared from the self-gelling powder provided by the present invention has a good hemostatic effect and good mechanical properties.

[0051] It should be noted that the "initial concentration" in the present invention refers to the concentration of the solutions of each raw material before the solution is mixed. The volume ratio of each solution in the mixed solution in this application refers to the ratio of each solution containing the substance of a certain concentration in the mixed solution. In the present invention, if the solvent is not specifically stated in the solution, the solvent is water.

[0052] The self-gelling powder provided by the present invention is obtained by mixing solution A, solution B and alkylated chitosan solution to obtain a mixed solution, and then freeze-drying the mixed solution and grinding to obtain the self-gelling powder; wherein the solution A includes PDDA and PEI; and the solution B includes PAA and PSS. The present invention selects alkylated chitosan solution as a raw material, selects specific solution A and solution B, uniformly mixes the three solutions, freeze-dries, and obtains the self-gelling powder. It is found through experiments that the alkylated chitosan provided by the present invention introduces a long-chain alkyl carbon chain on the amino group of the chitosan side chain, and the long carbon chain is similar to the polarity of the phospholipid bilayer of the cell membrane, so it can be embedded in the cell membrane to form a chitosan-blood cell gel network structure, which enhances the hemostatic effect of the powder. At the same time, the PDDA and PSS added by the present invention can form nanoparticles at the intersection of the polymer skeleton, so the hydrogel obtained by the prepared gelling powder has good mechanical strength; and the product form of the present application is a self-gelling powder, which is easy to carry and has a good market application prospect.

[0053] The following will be described clearly and completely in conjunction with the technical solutions of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] The raw materials provided by the present invention are as follows: PEI was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000; PDDA was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a weight average molecular weight of 100,000-200,000; PAA was purchased from Beijing Bailingwei Technology Co., Ltd. with a weight average molecular weight of 240,000; PSS was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000.

[0055] Example 1

[0056] Preparation of dodecyl-octadecyl chitosan.

[0057] 1. Accurately weigh 2.0 g of four groups of CS powder, add them to 100 mL of 2 wt% acetic acid solution, add 100 mL of ethanol after the chitosan is dissolved, put it in a 35°C water bath, and stir to mix to obtain a chitosan solution;

[0058] 2. Take dodecanedal and add it dropwise into the four groups of chitosan solutions according to the molar ratio of -NH2: -CHO = 1:0.125, stir and react for 4 hours, and then cool to room temperature;

[0059] 3. Accurately weigh NaBH3, dissolve it in pure water at a concentration of 0.1 g / mL, and slowly drip the NaBH3 solution into the reaction solution obtained in step 2 while stirring it continuously at a molar ratio of NaBH3:-CHO=3:1. Stir the reaction at room temperature for 3 hours.

[0060] 4. Add 4 wt % NaOH solution to the solution obtained in step 3 until pH = 10, precipitate the product, wash it by centrifugation at a speed of 8000 rad / min, wash it three times with methanol, wash it three times with ethanol, and wash it with water until it is neutral;

[0061] 5. Dissolve the product obtained in step 4 in 2 wt% acetic acid. After fully dissolved, store at 4°C for 30 min, filter out impurities under reduced pressure, add 4 wt% NaOH solution and stir until pH = 10, centrifuge at 8000 rad / min to separate the precipitate, and wash the precipitate with water until it is neutral;

[0062] 6. Step 5: freeze-dry the obtained product for 30 h to obtain four groups of different alkylated chitosans, named ACS-1, ACS-2, ACS-3, and ACS-4.

[0063] Example 2

[0064] The alkylated chitosan obtained in Example 1 was measured by infrared spectroscopy: the alkylated chitosan prepared was mixed with potassium bromide powder by KBr tableting method, ground into fine powder, and made into translucent thin slices by tableting machine, which were put into infrared spectrometer for testing, with the scanning range of 4000-400 cm -1 The infrared spectra of chitosan and alkyl chitosan are shown in Figure 1. Figure 1 This is the infrared spectrum of the alkylated chitosan prepared in Example 1 of the present invention; Figure 1 The black spectrum in the middle represents chitosan, and the red spectrum represents the prepared alkylated chitosan. It can be seen from the figure that compared with chitosan, the alkylated chitosan has a higher 1590cm -1 The characteristic peak of chitosan amino group disappeared, indicating that substitution reaction occurred at the N position. In addition, the peak at 1461cm -1 The new absorption peaks at , indicating that -CH2- and -CH3- groups have been introduced into chitosan molecules. The above results show that the grafting reaction does occur on the amino groups of chitosan, and the product obtained is alkylated chitosan.

[0065] Example 3

[0066] The effect of the ratio of polyethyleneimine (PEI) solution to polyacrylic acid (PAA) solution on gel strength was studied. PEI / PAA hydrogels were prepared, wherein the volume ratio of PEI solution to PAA solution was 3:7, 4:6, 5:5, 6:4, and 7:3, PEI was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, and PAA was purchased from Beijing Bailingwei Technology Co., Ltd. with a weight average molecular weight of 240,000.

[0067] 1. Prepare 35mL, 30mL, 25mL, 20mL, and 15mL of 5wt% PEI solution respectively and place them in different beakers.

[0068] 2. Prepare 15 mL, 20 mL, 25 mL, 30 mL, and 35 mL of 5 wt% PAA solution in different centrifuge tubes.

[0069] 3. Place a magnet in a beaker containing PEI solution and place the beaker on a magnetic stirrer.

[0070] 4. Start the magnetic stirrer and slowly pour the corresponding PAA solution into the PEI solution and PAA solution according to the volume ratio of 3:7, 4:6, 5:5, 6:4, and 7:3 after stabilization to mix the two evenly to prepare a hydrogel with a certain strength.

[0071] 5. Collect the hydrogels into different glass dishes, seal them with plastic wrap, and freeze them at -20°C overnight.

[0072] 6. Poke holes in the plastic wrap used for sealing and freeze-dry at -60°C for a total of 30 hours.

[0073] 7. Transfer the freeze-dried xerogel to a mortar and grind it into a fine powder.

[0074] Example 4

[0075] According to the technical scheme of Example 3, 5 groups of PEI / PAA gel powders with different volume ratios were prepared.

[0076] The PEI / PAA gel powder obtained in Example 3 was measured by rheometer: a Kinexus rheometer was used, and a plate with a diameter of 20 mm was selected to measure the modulus of each group of powders. 0.2 g of powder was taken from each group, 1 ml of distilled water was added, and the unabsorbed water was removed, and the powder was placed on the test plate. The modulus test program was selected, and the plate spacing was 0.8 mm under the conditions of fixed strain of 1.0%, frequency of 1.000 Hz, and the temperature was set to 37°C. The storage modulus (G') and loss modulus (G") of each of the five groups of products were measured. The results are shown in Figure 2 As shown, Figure 2 This is a test graph of the hydrogel modulus of PEI solution and PAA solution in different proportions prepared in Example 3 of the present invention;

[0077] As can be seen from the figure, when the volume ratio of PEI solution to PAA solution is 5:5, the formed hydrogel has the highest storage modulus and the best mechanical properties.

[0078] Example 5

[0079] The influence of the content of alkylated chitosan on the hemostatic ability and mechanical strength of the gel was studied. The concentration of alkylated chitosan was set to 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, and the volume accounted for 10% of the total system. The concentration of PDDA solution was fixed to 8wt% and the concentration of PSS solution was fixed to 10.3wt%, each accounting for 5% of the total system. PEI was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, PDDA was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a weight average molecular weight of 100,000-200,000; PAA was purchased from Beijing Bailingwei Technology Co., Ltd. with a weight average molecular weight of 240,000, PSS was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, and the alkylated chitosan was the dodecyl chitosan prepared in Example 1.

[0080] 1. Prepare five mixed solutions containing 22.5 mL of 5 wt% PEI solution and 2.5 mL of 8 wt% PDDA solution as solution A and place them in a beaker.

[0081] 2. Prepare five mixed solutions containing 22.5 mL of 5 wt% PAA solution and 2.5 mL of 10.3 wt% PSS solution as solution B and place them in centrifuge tubes.

[0082] 3. Prepare 5 mL of 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% and 1.0wt% alkylated chitosan solutions and place them in centrifuge tubes respectively.

[0083] 4. Place the magnet in the beaker containing solution A and place the whole on a magnetic stirrer.

[0084] 5. Start the magnetic stirrer, and after it stabilizes, slowly pour solution B and the corresponding alkylated chitosan solution into the mixture to mix the three evenly to prepare a hydrogel with a certain strength.

[0085] 6. Collect the hydrogel into a glass dish, seal it with plastic wrap, and freeze it at -20℃ overnight.

[0086] 7. Poke holes in the plastic wrap used for sealing and freeze-dry at -60°C for a total of 30 hours.

[0087] 8. Transfer the freeze-dried xerogel to a mortar and grind it into a fine powder.

[0088] Example 6

[0089] Gel powders with different alkylated chitosan contents were prepared according to Example 5, and the modulus of the gel powders obtained in Example 5 was measured by rheometer: a Kinexus rheometer was used, and a plate with a diameter of 20 mm was selected to measure the modulus of each group of powders. 0.2 g of powder was taken from each group, 1 ml of distilled water was added, and the unabsorbed water was removed, and the powders were placed on the test plate. The modulus test procedure was selected, and the plate spacing was 0.8 mm under the conditions of fixed strain of 1.0%, frequency of 1.000 Hz, and the temperature was set to 37°C for testing. The storage modulus (G') and loss modulus (G") of each of the five groups of products were measured. The results are shown in FIG. Figure 3 As shown, Figure 3 This is a test graph of the modulus of hydrogels with different ACS contents prepared in Example 5 of the present invention; it can be seen from the figure that the alkylated chitosan content is inversely proportional to the storage modulus (G') of the hydrogel, indicating that as the ACS content increases, the mechanical strength of the formed hydrogel will decrease.

[0090] Prepare gel powders with different alkylated chitosan contents according to Example 5, and measure the viscosity stress of the gel powder obtained in Example 5 by a tensile testing machine: Use an intelligent electronic tensile testing machine, select the tensile strength test mode, and test the viscosity stress of each group of powders. Take 0.4g of powder from each group and make a hydrogel strip with a length of 4cm, a width of 1cm, and a thickness of 2mm. Take pig skin that has been washed of grease and make it of the same size, and bond one end of the hydrogel to the outside of the pig skin. The two overlap to form a strip, and the overlapping area is 1cm 2 , a 200g weight was pressed on the overlap of the hydrogel and the pigskin for 20 minutes. Then the test was carried out using a tensile testing machine with a fixed tensile speed of 25mm / min until the hydrogel and the pigskin were completely pulled apart, and the maximum tensile force was recorded. The viscosity stress is the maximum tensile force divided by the overlapping area between the hydrogel and the pigskin. The results are as follows Figure 4 As shown, Figure 4 This is a viscosity test graph of different alkylated chitosan contents prepared in Example 5 of the present invention; the results show that the alkylated chitosan content is proportional to the viscosity stress of the hydrogel, indicating that as the alkylated chitosan content increases, the adhesion of the hydrogel to the skin increases accordingly.

[0091] Conclusion: In order to balance the mechanical strength, hemostatic ability and skin adhesion of the hydrogel, 0.6wt% was selected as the optimal concentration of the alkylated chitosan solution.

[0092] Example 7

[0093] The effects of PDDA and PSS contents on the hemostatic ability and mechanical strength of the gel were studied. 8wt% PDDA solution and 10.3wt% PSS solution each accounted for the same proportion in the total system, and a total of five groups were set, namely 3%, 4%, 5%, 6%, and 7%. PEI was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, PDDA was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a weight average molecular weight of 100,000-200,000; PAA was purchased from Beijing Bailingwei Technology Co., Ltd. with a weight average molecular weight of 240,000, PSS was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, and alkylated chitosan was the dodecyl chitosan prepared in Example 1.

[0094] 1. Prepare five groups of 5wt% PEI solutions with volumes of 21mL, 20.5mL, 20mL, 19.5mL, and 19mL, and mix them evenly with 1.5mL, 2mL, 2.5mL, 3mL, and 3.5mL of 8wt% PDDA solution, respectively, totaling 45mL, and place them in a beaker as solution A.

[0095] 2. Prepare five groups of 5 wt% PAA solutions with volumes of 19 mL, 19.5 mL, 20 mL, 21.5 mL, and 22 mL, and mix them evenly with 1.5 mL, 2 mL, 2.5 mL, 3 mL, and 3.5 mL of 10.3 wt% PSS solution, respectively, totaling 45 mL, and place them in a centrifuge tube as solution B.

[0096] 3. Prepare five groups of 5 mL 0.6 wt% alkylated chitosan solution and place them in centrifuge tubes respectively.

[0097] 4. Place the magnet in the beaker containing solution A and place the whole on a magnetic stirrer.

[0098] 5. Start the magnetic stirrer, and after it stabilizes, slowly pour the corresponding solution B and the alkylated chitosan solution into the mixture to mix the three evenly to prepare a hydrogel with a certain strength.

[0099] 6. Collect the hydrogels into different glass dishes, seal them with plastic wrap, and freeze them at -20°C overnight.

[0100] 7. Poke holes in the plastic wrap used for sealing and freeze-dry at -60°C for a total of 30 hours.

[0101] 8. Transfer the freeze-dried xerogel to a mortar and grind it into a fine powder.

[0102] Example 8

[0103] Gel powders with different PDDA and PSS contents were prepared according to Example 7, and the modulus of the gel powders obtained in Example 7 was measured by rheometer: a Kinexus rheometer was used, and a plate with a diameter of 20 mm was selected to measure the modulus of each group of powders. 0.2 g of powder was taken from each group, 1 ml of distilled water was added, and the unabsorbed water was removed, and the powders were placed on the test plate. The modulus test procedure was selected, and the plates were spaced 0.8 mm apart and the temperature was set to 37°C under the conditions of fixed strain of 1.0% and frequency of 1.000 Hz to measure the storage modulus (G') and loss modulus (G") of each of the five groups of products. The results are shown in Figure 2. Figure 5 As shown, Figure 5 This is a test graph of the hydrogel modulus with different PDDA and PSS contents prepared in Example 7 of the present invention;

[0104] It can be seen from the figure that the content of PDDA and PSS is proportional to the storage modulus (G') of the hydrogel, indicating that the mechanical strength of the formed hydrogel will be enhanced as the content of PDDA and PSS increases.

[0105] According to Example 7, gel powders with different PDDA and PSS contents were prepared, and the viscosity stress of the gel powders obtained in Example 7 was measured by a tensile testing machine: an intelligent electronic tensile testing machine was used, and the tensile strength experimental mode was selected to test the viscosity stress of each group of powders. 0.4 g of powder was taken from each group and made into hydrogel strips with a length of 4 cm, a width of 1 cm, and a thickness of 2 mm. Pigskin that had been washed free of grease was made into the same size, and one end of the hydrogel was bonded to the outside of the pigskin. The two overlapped to form a long strip, and the overlapping area was 1 cm 2 , a 200g weight was pressed on the overlap of the hydrogel and the pigskin for 20 minutes. Then the test was carried out using a tensile testing machine with a fixed tensile speed of 25mm / min until the hydrogel and the pigskin were completely pulled apart, and the maximum tensile force was recorded. The viscosity stress is the maximum tensile force divided by the overlapping area between the hydrogel and the pigskin. The results are as follows Figure 6 As shown, Figure 6 This is a viscosity test chart of different PDDA and PSS contents prepared in Example 7 of the present invention; the results show that the contents of PDDA and PSS are inversely proportional to the viscosity stress of the hydrogel, indicating that as the contents of PDDA and PSS increase, the adhesion of the hydrogel to the skin decreases.

[0106] Conclusion: Combining the mechanical properties test results and viscosity test results, 5% PDDA and PSS volume ratio was finally selected as the optimal solution.

[0107] Example 9

[0108] According to the technical schemes of Examples 1 to 8, four groups of self-gelling powders containing different alkylated chitosans formed in situ were prepared, wherein the four alkylated chitosans were dodecyl chitosan, tetradecyl chitosan, hexadecyl chitosan, and octadecyl chitosan.

[0109] The concentration of PEI and PAA is 5wt%, the volume ratio is 5:5, and they account for 40% of the total system volume respectively. The mass concentration of different alkylated chitosans is 0.6wt%, accounting for 10% of the total system volume; the mass concentration of PDDA is 8wt%, and the concentration of PSS is 10.3wt%, accounting for 5% of the total system volume respectively. PEI was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, PDDA was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a weight average molecular weight of 100,000-200,000; PAA was purchased from Beijing Bailingwei Technology Co., Ltd. with a weight average molecular weight of 240,000, and PSS was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000. The alkylated chitosans are the four alkylated chitosans prepared in Example 1.

[0110] 1. Prepare four mixed solutions containing 22.5 mL of 5 wt% PEI solution and 2.5 mL of 8 wt% PDDA solution as solution A and place them in a beaker.

[0111] 2. Prepare four mixed solutions containing 22.5 mL of 5 wt% PAA solution and 2.5 mL of 10.3 wt% PSS solution as solution B and place them in centrifuge tubes.

[0112] 3. Prepare four different groups of alkylated chitosan solutions into 5 mL of 0.6 wt% solution and place them in centrifuge tubes respectively.

[0113] 4. Place the magnet in the beaker containing solution A and place the whole on a magnetic stirrer.

[0114] 5. Start the magnetic stirrer, and after it stabilizes, slowly pour solution B and the corresponding alkylated chitosan solution into the mixture to mix the three evenly to prepare a hydrogel with a certain strength.

[0115] 6. Collect the hydrogel into a glass dish, seal it with plastic wrap, and freeze it at -20℃ overnight.

[0116] 7. Poke holes in the plastic wrap used for sealing and freeze-dry at -60°C for a total of 30 hours.

[0117] 8. Transfer the freeze-dried xerogel to a mortar and grind it into a fine powder.

[0118] Example 10

[0119] Four groups of in-situ self-gelling powders containing different alkylated chitosans prepared according to Example 9 were tested for their gel transformation speeds and grouped as ACS-1, ACS-2, ACS-3, and ACS-4. The gel transformation time of different groups was measured by timing: 1.0 g of powder from each group was placed in a culture dish with a diameter of 3.0 mm, and the powder was evenly spread. A proper amount of physiological saline was taken with a pipette or a disposable rubber-tipped dropper and added to the culture dish containing the powder, and a timer was used to accurately time the time. Each group of samples was repeated three times.

[0120] The results are shown in Table 1 and Figure 7 As shown, Figure 7 It is the gel transformation time of the in situ self-gelling powder containing different alkylated chitosans; it can be seen from the figure and the table that due to the hydrophobic nature of the alkyl group and the difference in the length of the carbon chain, the gel transformation time of the dodecyl chitosan group is the fastest, which is faster than the existing literature reports, and the octadecyl chitosan gel transformation time is the slowest.

[0121] Table 1 Gel transition time of in situ self-gelling powders containing different alkylated chitosans

[0122]

[0123] Conclusion: According to the test results of gel conversion time of each group, dodecyl chitosan was finally selected as the optimal solution.

[0124] Embodiment 11

[0125] According to the technical scheme of Examples 1 to 10, an in-situ self-gelling powder is prepared, such as Figure 8 . Figure 8 The schematic diagram of hydrogel synthesis is shown in the figure; the concentration of PEI and PAA is 5wt%, the volume ratio is 5:5; they account for 40% of the total system volume respectively, the mass concentration of alkylated chitosan is 0.6wt%, accounting for 10% of the total system volume; the mass concentration of PDDA is 8wt%, and the concentration of PSS is 10.3wt%, accounting for 5% of the total system volume respectively. PEI was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, PDDA was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a weight average molecular weight of 100,000-200,000; PAA was purchased from Beijing Bailingwei Technology Co., Ltd. with a weight average molecular weight of 240,000, PSS was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a weight average molecular weight of 70,000, and the alkylated chitosan was the dodecyl chitosan prepared in Example 1.

[0126] 1. Prepare 5wt% PEI solution and 8wt% PDDA solution, mix them evenly as solution A and place them in a beaker.

[0127] 2. Prepare 5 wt% PAA solution and 10.3 wt% PSS solution, mix them evenly as solution B and place them in a centrifuge tube.

[0128] 3. Prepare 0.6 wt% alkylated chitosan solution and place it in centrifuge tubes respectively.

[0129] 4. Place the magnet into the beaker containing mixed solution A, place the whole on a magnetic stirrer, start the magnetic stirrer, and after it stabilizes, slowly pour in the mixed solution B and alkylated chitosan solution to mix the three evenly to form a hydrogel.

[0130] 5. Collect the hydrogel into a glass dish, seal it with plastic wrap, and freeze it at -20℃ overnight.

[0131] 6. Poke holes in the plastic wrap used for sealing and freeze-dry at -60°C for a total of 30 hours.

[0132] 7. Transfer the freeze-dried xerogel to a mortar and grind it into a fine powder.

[0133] The present invention observes the physical morphology and internal structure of the powder by photographing the actual powder and SEM images. Fig. 9 As shown, Fig. 9 The image and scanning electron microscope image of the in-situ self-gelling powder prepared in Example 11 of the present invention; wherein, Fig. 9 The left image is a gel powder image, and the right image is a scanning electron microscope image. Fig. 9 It can be seen that the self-gelling powder prepared by the present invention has a fine appearance, can be ground into finer powder, has a loose porous structure inside, and has good moisture absorption performance.

[0134] Test Case

[0135] 1. Safety evaluation of in-situ self-gelling powder

[0136] 1.1. Hemolysis rate experiment: centrifuge the anticoagulated whole blood at 3000rpm for 10min at 4℃, remove the upper plasma and the light yellow part, and wash the bottom red blood cells with PBS until the upper solution is colorless. After that, prepare a 2% red blood cell suspension with PBS. Take 2mg PEI / PAA gel powder, ACS powder, PEI / PAA / ACS gel powder, (PEI / PDDA) / (PAA / PSS) / ACS gel powder and place them in 4 EP tubes, add 1ml PBS to each, soak at 37℃ shaker for 24h, and then take out the leaching solution for use. Mix 500μL of this 2wt% red blood cell suspension with equal volumes of PBS (negative control) and deionized water (positive control) and 4 groups of leaching solutions, and incubate at 37℃ for 2h. The incubated sample and red blood cell mixture was centrifuged at 3000 rpm for 5 min, the supernatant was collected, and the absorbance at 570 nm was detected by an ELISA instrument. The test was repeated three times, and the hemolysis rate of each group was calculated according to the following formula.

[0137]

[0138] Where, Hemolysis is the hemolysis rate; Abs, Abs0, Abs l These are the absorbance values ​​after the reaction of 4 groups of samples, PBS, and deionized water with red blood cells.

[0139] The experimental results are shown in Table 1 and Fig.10 As shown, Fig.10 The hemolysis rate results of the prepared self-gelling powder and its components; the hemolysis rates of the ACS powder and the prepared self-gelling powder are both <2.5%, which is in line with the provisions of the national drug packaging material standard YBB00032003-2015 hemolysis test method (the sample hemolysis rate should not exceed 5%).

[0140] Table 2 Hemolysis rate test results of the self-gelling powder and its components prepared in the embodiment of the present invention

[0141]

[0142] 1.2. Cytotoxicity experiment: MTT assay was performed using co-culture of mouse fibroblasts L929. First, the sample extract was prepared with DMEM culture medium. 2 mg of PEI / PAA gel powder, ACS powder, PEI / PAA / ACS gel powder, and (PEI / PDDA) / (PAA / PSS) / ACS gel powder were taken. After 24 hours of ultraviolet irradiation disinfection, 1 mL of DMEM culture medium was added to each sample and soaked at 37°C for 24 hours. The extract was taken out, filtered and sterilized with a 0.45 μm filter membrane, and 500 μL was added to an equal volume of DMEM culture medium containing 20% ​​fetal bovine serum (FBS). After L929 cells were digested with 0.25 wt% trypsin at 37°C for 1 min, the cells were resuspended with culture medium, and the cell density was adjusted to 5×10 4 / mL, 100μL L929 cells were added to each well and seeded in a 96-well plate, and placed in an incubator containing 5% CO2 by volume and a temperature of 37°C for 24h; after 24h, 100μL of sample extract was added to the culture medium, and a normal culture control group was set up, and the plates were placed in a CO2 incubator for further culturing for 48h; after 48h, a portion of the cells was taken, the original culture medium was discarded, 100μL of sterile culture medium and 10μL of sterile MTT solution were added to the 96-well plate, and the plates were placed in an incubator for further culturing for 4h; MTT and culture medium were discarded, SDS lysis solution was added to repeatedly dissolve the precipitate, and the absorbance at 490nm was measured with an enzyme marker, and the cell proliferation rate of each group was calculated according to the following formula.

[0143]

[0144] Wherein, RGR is the relative proliferation rate of cells; A0 is the absorbance value of the solvent control group; A1 is the absorbance value of the normal culture control group; A2 is the absorbance value of the experimental group.

[0145] The results of the cell proliferation rate experiment are shown in Table 2 and Fig.11 As shown, Fig.11 The results of cell proliferation rate of the self-gelling powder and its components are as follows; the cell proliferation rates of the four groups of PEI / PAA gel powder, ACS powder, PEI / PAA / ACS gel powder, and (PEI / PDDA) / (PAA / PSS) / ACS gel powder were all greater than 80%, and the cytotoxicity grade was 1. The results showed that PEI / PAA gel powder, ACS powder, PEI / PAA / ACS gel powder, and (PEI / PDDA) / (PAA / PSS) / ACS gel powder all showed good biocompatibility.

[0146] Table 3 Test results of cell proliferation rate of self-gelling powder and its components prepared in the examples of the present invention

[0147]

[0148] 1.3. Evaluation of antibacterial properties: Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were selected as Gram-positive bacteria and Gram-negative bacteria, respectively, for antibacterial tests. First, the material was mixed with 5 mL of bacterial suspension (1×10 4 CFU / mL) in a sterile tube and incubate at 37°C in a shaker for 24 h. Dilute the incubated bacterial suspension by 10 6 The bacteria were coated on the surface of solid agarose medium and placed in a 37°C incubator for 24 hours. The number of surviving bacteria was recorded by counting the colonies on the solid agarose medium. The bacteria that had not been treated were used as the control group to calculate the inhibition rate. The experimental results are shown in Table 4 and Fig.12 As shown: the positive drug chitosan has obvious antibacterial effect on Staphylococcus aureus and Escherichia coli, and the inhibition rates of Escherichia coli and Staphylococcus aureus are 94.64% and 98.26% respectively; the improved alkylated chitosan also shows good antibacterial effect, and the inhibition rates of Escherichia coli and Staphylococcus aureus are 86.51% and 93.66% respectively; the PEI / PAA gel powder itself has no bactericidal effect, but because the powder itself is water-absorbent, it changes the living environment of bacteria, slows down the growth rate of bacteria, and the colony count is lower than other groups; the gel powders with added alkylated chitosan all show excellent antibacterial effect, with an antibacterial rate of up to 99%.

[0149] Table 4 Antibacterial performance test results of the self-gelling powder and its components prepared in the embodiment of the present invention

[0150]

[0151]

[0152] 1.4. Evaluation of hemostasis and healing effects

[0153] In vitro coagulation test: 5 mg of sample was placed in a 96-well plate, 100 μL of anticoagulant blood was added, 10 μL of CaCl2 solution (concentration of 0.2 mol / L) was added, and the timing was started at the same time. PBS was aspirated and rinsed with a pipette every 30 seconds, and the coagulation was observed until the blood was completely coagulated. When there was no change after multiple rinses, the whole blood coagulation time was recorded. Each sample was repeated 3 times, and the blood without sample addition was used as the control group. The results of the in vitro coagulation test are shown in Table 4 and Fig.13 , 14 As shown, Fig.13 In vitro clotting time of the self-gelling powder and its components obtained for preparation; Fig.14The figure is a real picture of the in vitro coagulation of the self-gelling powder and its components. Compared with the blank, the PEI / PAA gel powder, ACS powder, PEI / PAA / ACS gel powder, (PEI / PDDA) / (PAA / PSS) / ACS gel powder prepared by the present invention have improved coagulation effect compared with zeolite powder.

[0154] Table 5 In vitro coagulation test results of the self-gelling powder and its components prepared in the embodiments of the present invention

[0155]

[0156] 1.5. Evaluation of wound healing effect

[0157] Evaluation of wound healing effect: 20 SD rats were randomly divided into 4 groups and adaptively cultured for one week. The rats were anesthetized with 10% chloral hydrate at a dose of 0.3mL / 100g, fixed on the operating table, and the hair on the back of the rats was cleaned with a depilatory cream. After disinfection with 75% alcohol, a biopsy sampler with a diameter of 10 mm was used to make a dorsal wound model of SD rats. The prepared bacterial solution was applied to the wound surface, and different powders were applied to the wound for treatment. PBS was used as the control group. On days 0, 2, 4, 7 and 10, the wound healing status of each group was observed and photographed. The experimental results are shown below. Fig.15 As shown, compared with the PBS group, the wound healing degree of the PEI / PAA powder group was not significantly enhanced, while the wound area treated with PEI / PAA / ACS gel powder and (PEI / PDDA) / (PAA / PSS) / ACS gel powder was significantly reduced in the same period of time, and the healing degree was enhanced.

[0158] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A self-gelling powder, which is prepared by mixing a solution A, a solution B and an alkylated chitosan solution to obtain a mixed solution, and then freeze-drying the mixed solution and grinding it to obtain the self-gelling powder; in, The A solution includes a polydimethyl ammonium chloride solution and a polyethyleneimine solution; The B solution includes sodium polystyrene sulfonate solution and polyacrylic acid solution; The initial concentration of the polyethyleneimine solution is 5-8 wt %, and the initial concentration of the polydiallyl dimethyl ammonium chloride solution is 7-12 wt %; In the mixed solution, the polydiallyl dimethyl ammonium chloride solution accounts for 3-7% of the total volume, and the polyethyleneimine solution accounts for 38-42% of the total volume; The initial concentration of the polyacrylic acid solution is 5-8wt%, and the initial concentration of the sodium polystyrene sulfonate solution is 9-12wt%; In the mixed solution, the sodium polystyrene sulfonate solution accounts for 3-7% of the total volume, and the polyacrylic acid solution accounts for 38-42% of the total volume; The alkylated chitosan is one or more of dodecyl chitosan, tetradecyl chitosan, hexadecyl chitosan and octadecyl chitosan; The initial concentration of the alkylated chitosan solution is 0.2wt% to 1wt%; In the mixed solution, the alkylated chitosan solution accounts for 8-15% of the total volume.

2. The self-gelling powder according to claim 1, characterized in that The initial concentration of the polyacrylic acid solution is 6-7 wt %, and the initial concentration of the sodium polystyrene sulfonate solution is 10-11 wt %.

3. Use of the self-gelling powder according to any one of claims 1 to 2 in the preparation of wound treatment materials.

Citation Information

Patent Citations

  • Alkylated chitosan hemostatic microcapsule and preparation method thereof

    CN113209359A

  • Composition with functions of promoting wound healing and rapidly stopping bleeding

    CN114848668A